Modification of Catfish Feed with the Addition of Microbacteria from Banana Peel Fermentation - Nyiur Salsabila Frida; Khansa Nabilatus Syafiqoh; Shofiatur Rahmah; Melati Helga Utami; Nadia Zulfaa; Agus Widayoko (SMA Trensains Muhammadiyah Sragen, 2022)
Catfish (Clarias sp.) is one of the freshwater fishery commodities that are in great demand in Indonesia so that production stability must be maintained every year. Efforts are being made to increase catfish production, namely through the provision of microbacteria from fermented banana peels in feed. This study aims to examine the effect of giving cultured microbacteria in different media to feed on the specific growth rate (SGR) in catfish. The type of research used is experimental. Data collection is done by observation and tests. Observations were made during the manufacture of modified feed, while tests were used to examine differences in catfish growth. The results showed that catfish fed with the addition of Banana Peel Fermented Microbacteria experienced a faster growth when compared to catfish with regular feed in a ratio of 2:1.